A Study of Financial Performance and Stock Return in IPO Underpricing Phenomenon on the Indonesia Stock Exchange (IDX) - Irfani, Agus (UI Scholars Hub, 2012)
It is widely believed that ﬁnancial performance of listed companies on stock exchange might potentially affect long-term stock return. However, the impact of ﬁnancial performance on underpric-ing is still in debate. The purpose of this study is to examine the effect of ﬁnancial performance on underpricing at the same period and the effect of both ﬁnancial performance and underpricing on the long-term stock return on the Indonesia stock exchange (IDX). By employing judgemental sampling method, the sample of this reseach includes 43 underpriced stocks taken from the population of 51 initially public offered stocks on the IDX during 2008-2010. This research uses multiple regression technique to test the hypothesis. This study concludes that not all ﬁnancial performance ratios affect the underpricing and the long-term stock return in 2011. In addition, this study does not ﬁnd any em-pirical evidence about the effect of underpricing on the long-term stock return.